Cortical modulation of short-latency TMS-evoked potentials - Veniero, Domenica; Bortoletto, Marta; Miniussi, Carlo (Frontiers in Human Neuroscience, 2013)
Transcranial magnetic stimulation - electroencephalogram (TMS-EEG) co-registration offers the opportunity to test reactivity of brain areas across distinct conditions through TMS-evoked potentials (TEPs). Several TEPs have been described, their functional meaning being largely unknown. In particular, short-latency potentials peaking at 5 (P5) and 8 (N8) ms after the TMS pulse have been recently described, but because of their huge amplitude, the problem of whether their origin is cortical or not has been opened. To gain information about these components, we employed a protocol that modulates primary motor cortex excitability (MI) through an exclusively cortical phenomena: low frequency stimulation of premotor area (PMC). TMS was applied simultaneously with EEG recording from 70 electrodes. Amplitude of TEPs evoked by 200 single-pulses TMS delivered over MI at 110% of resting motor threshold was measured before and after applying 900 TMS conditioning stimuli to left premotor cortex with 1 Hz repetition rate. Single subject analyses showed reduction in TEPs amplitude after PMC conditioning in a sample of participants and increase in TEPs amplitude in two subjects. No effects were found on corticospinal excitability as recorded by motor evoked potentials (MEPs). Furthermore, correlation analysis showed an inverse relation between the effects of the conditioning protocol on P5-N8 complex amplitude and MEPs amplitude. Because the effects of the used protocol have been ascribed to a cortical interaction between premotor area and MI, we suggest that despite the sign of P5-N8 amplitude modulation is not consistent across participant, this modulation could indicate, at least in part, their cortical origin. We conclude that with an accurate experimental procedure early-latency components can be used to evaluate the reactivity of the stimulated cortex.